Students' Needs and Preferences for Digital EFL Learning Materials - Herman, Mulyati; Regina, Regina; Yuliana, Yohanes Gatot Sutapa (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
While research on digital language learning materials has received lots of attention, there was a scarcity of studies focusing on specific locations, like Sambas in West Kalimantan, Indonesia. Located near the border of Indonesia and Malaysia, Sambas has a unique EFL learning environment influenced by its geographical location and diverse socio-economic backgrounds. Understanding students' needs and preferences in local contexts is crucial in designing culturally relevant teaching materials. This study aimed to assess the needs and preferences of students in Sambas and provided valuable insights into optimizing the utilization of digital teaching materials for English language learning. This study employed a survey research design to elicit information about current materials, the student's needs, perceptions, and preferences concerning digital materials in English students' needs and preferences, and technological resources. The participants of this study were first-year students of junior secondary school (20 students) in Sambas. The findings revealed that students need videos, movies, and songs with English subtitles as learning materials. Furthermore, the study might shape future research in developing and implementing digital EFL materials customized to the Sambas' cultural context, including local language, customs, and traditions, and their effectiveness in engaging students and improving English language acquisition.